2015
DOI: 10.1080/14330237.2015.1021515
|View full text |Cite
|
Sign up to set email alerts
|

“Whenever Jack sees a condom, he falls asleep”: experiences of condom use and erectile disorder among HIV positive men in a Zimbabwean rural setting

Abstract: In this qualitative inquiry, we set out to explore the experience of condom use and erectile disorder (ED) among men living with HIV in a rural district of Zimbabwe. Data on condom use related erectile disorder with antiretroviral (ART) medication were collected from a purposive sample of 18 men living with HIV and AIDS (age range 23-54 years). These data were supplemented with those from a convenience sample of 23 women living with HIV who self-identified as partners of men living with HIV and AIDS (age range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This qualitative inquiry was part of a series of studies conducted on socio-cultural realities of following through with PMTCT in Chiota rural community, Zimbabwe (e.g., Nyati-Jokomo, January, Mpande, & Ruparanganda, 2015). The qualitative method was selected to understand the meanings that people attach to phenomena within their social worlds as indicated by Denzin, Lincoln, and Lincoin (2000).…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative inquiry was part of a series of studies conducted on socio-cultural realities of following through with PMTCT in Chiota rural community, Zimbabwe (e.g., Nyati-Jokomo, January, Mpande, & Ruparanganda, 2015). The qualitative method was selected to understand the meanings that people attach to phenomena within their social worlds as indicated by Denzin, Lincoln, and Lincoin (2000).…”
Section: Methodsmentioning
confidence: 99%
“…This paper reports results from part of a larger study on socio-cultural realities of following through with PMTCT in the Chiota rural community in Zimbabwe [13, 14]. Results from this study were reported using the Consolidated Criteria for Reporting Qualitative Research (COREQ) [15].…”
Section: Methodsmentioning
confidence: 99%
“…Participation was voluntary and participants were recruited at two government primary healthcare facilities as they came to collect their monthly supplies of medication or when they came for the child welfare clinics. Stigma surrounding HIV and AIDS is still very strong in the area under study such that efforts to recruit mothers from the community became futile, hence the resolution to recruit from the health facilities [13].…”
Section: Methodsmentioning
confidence: 99%